Symbolizing Desire: Barong and Rangda Performance in a Balinese Hindu Newborn Ritual - I Gede Suwantana; I Made Girinata; I Putu Agus Aryatnaya Giri; Sudip Chakravortti (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
Although Barong–Rangda is widely recognized today as a touristic performance linked to Bali’s cultural tourism, its sacred ritual functions continue in Bali, showing that commodification has not erased its religious significance. This article examines the nyambutin ritual, a Balinese Hindu ceremony welcoming newborn babies, focusing on the inclusion of Barong–Rangda performance in a traditional Balinese village. Using ethnographic observation, in-depth interviews, and textual analysis, the study applies semiotic perspectives from Barthes, Eco, and Peirce to interpret the ritual’s symbolic meanings. The findings show that Barong and Rangda represent disciplined and uncontrolled forms of desire, reflecting moral tensions within Balinese cosmology. The performance functions as embodied moral education, introducing ethical values through ritual experience rather than verbal instruction. Sustained by local ritual authority, the tradition continues as religious knowledge transmission while resisting full commodification despite the global circulation of Barong imagery through tourism.